(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This study describes the approach to e- learning and Realization for people with disabilities, especially the Hearing Impair. The researcher is trying in this research that measure the effectiveness and impact of e-learning on the Hearing Impaired, By knowing the different educational problems faced by the hearing impaired and try to eliminate these problems by applying them to an e-educational program in one of the subjects and find the difference before and after the application of the program. If the results are, positive we try to apply this method in their educational lives and this provides a lot for the hearing impaired (integrated educational environment of the cadres of education and educational presentations of lessons and exercises appropriate to the number of times many training and examinations) and the teacher’s role here is different from previously. The teacher’s role here will be the facilitator of the educational process. This helps the hearing-impaired integration in the Egyptian society and not linked to the idea of sign language and education in order to participate Hearing Impaired any kind of education or different cultures with the Egyptian society through e -learning.